The ecology of small mammals (Rodentia, Insectivora) in the coastal mountain fynbos of the southwestern Cape - Pretorius, Esther Catharina (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.